Diversidade genética de macrophomina phaseolina e o efeito do óleo essencial de cymbopogon flexuosus no seu crescimento in vitro - Dias, Atarrissis Morais (Universidade Federal Rural do Semi-Árido, 2020)
The fungus Macrophomina phaseolina is considered one of the main etiological agents of the collapse of the branches, one of the main diseases that affect the culture of the melon. This pathogen is considered difficult to control and due to this factor, studies are needed to help understand its genetic variation and control alternatives. The objectives of this study were to evaluate the genetic diversity of M. phaseolina isolates and to verify the effect of Cymbopogon flexuosus essential oil (Indian lemon grass) on in vitro growth of isolates 5 and 29. The DNAs of the 30 isolates were extracted according to the NucleoSpin Microbial DNA extraction kit protocol. Of the 100 primers pre-analyzed, 13 primers from the Random Amplified Polymorphic DNA (RAPD) marker were selected to perform genetic diversity. The analyzes for obtaining the dendogram were performed using the NTSYS program. All isolates were confirmed by molecular analysis from specific gene primers that amplified specific DNA bands of approximately 350 bp. A total of 135 bands were amplified where 97 (71.85%) were considered polymorphic with an average of 7.5 polymorphic fragments per primer. The degree of genetic similarity ranged from 0.23 to 0.92, whose co-phenetic correlation value was r = 0.84, which demonstrates the presence of genetic variability between the isolates and a good reliability between the matrix data and the dendogram. The generated dendogram indicated the formation of four main groups among the isolates which were not grouped according to the origin or place of collection. This fact may be related to the evolution of ancestors between the groups. The analyzes with the essential oil (OE) of C. flexuosus were conducted in a completely randomized experimental design (DIC), with two distant isolates genetically (5 and 29), six concentrations of OE (0.02; 0.05; 0.10; 0.15; 0.20 and 0.25%) a negative control (BDA medium) and a positive control (BDA medium + Maxim fungicide) with eight repetitions for each treatment. Daily measurements of the colony diameter were performed in two perpendicular directions. The data obtained were interpreted using a fourparameter logistic equation and the averages were compared using the Mann Whitney test, at 5% probability. In the essential oil of C. flexuosus from the concentration 0.15%, there was a total inhibition in growth in vitro in the two isolates of M. phaseolina evaluated. This represents a promising result regarding the future use of essential oil to control the pathogen. There was no statistically significant difference in the essential oil of C. flexuosus in isolates 5 and 29, which demonstrates the efficiency of this OE between the two isolates studied. With this work it can be concluded that the RAPD marker was considered adequate to assess the genetic diversity of the studied isolates and that the C. flexuosus OE was considered efficient in inhibiting growth in vitro in the evaluated M. phaseolina isolates
Keywords: Capim limão indiano; Fungo; PCR; RAPD; Indian lemon grass; Fungi; PCR; RAPD; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA